2021
DOI: 10.1182/blood.2020008738
|View full text |Cite
|
Sign up to set email alerts
|

RhoG deficiency abrogates cytotoxicity of human lymphocytes and causes hemophagocytic lymphohistiocytosis

Abstract: Exocytosis of cytotoxic granules (CG) by lymphocytes is required for the elimination of infected and malignant cells. Impairments in this process underly a group of diseases with dramatic hyperferritinemic inflammation termed hemophagocytic lymphohistiocytosis (HLH). Although genetic and functional studies of HLH have identified proteins controlling distinct steps of CG exocytosis, the molecular mechanisms that spatiotemporally coordinate CG release remain unclear. We studied a patient exhibiting characteristi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
3

Relationship

3
7

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 59 publications
1
40
0
Order By: Relevance
“…Following cell activation and formation of the IS, vesicles containing RAB27A, vesicles containing MUNC13-4, and CGs co-localize at the IS and fuse into a common vesicular structure ( 26 ). While RAB27A mediates the docking of these CGs, MUNC13-4, itself tethered to the membrane via a required protein-protein interaction with the small GTPase RhoG ( 27 ), is required for the final step prior to granule fusion with the plasma membrane. This final process, known as priming, makes these granules competent for exocytosis ( 9 ).…”
Section: Biology Of the Degranulation Pathwaymentioning
confidence: 99%
“…Following cell activation and formation of the IS, vesicles containing RAB27A, vesicles containing MUNC13-4, and CGs co-localize at the IS and fuse into a common vesicular structure ( 26 ). While RAB27A mediates the docking of these CGs, MUNC13-4, itself tethered to the membrane via a required protein-protein interaction with the small GTPase RhoG ( 27 ), is required for the final step prior to granule fusion with the plasma membrane. This final process, known as priming, makes these granules competent for exocytosis ( 9 ).…”
Section: Biology Of the Degranulation Pathwaymentioning
confidence: 99%
“…At this stage, we cannot generalize the case of ARPC1B deficiency in establishing a systematic relationship between IS alteration and functional defects. However, it is interesting that multiple IEIs have been found by us and others to be associated with IS defects and functional impairment (Gil-Krzewska et al, 2018;Kalinichenko et al, 2021;Pfajfer et al, 2017;Salzer et al, 2016). Previous reports have also shown that IEIs where the IS is defective fail to eliminate target cells Mizesko et al, 2013;Pfajfer et al, 2017).…”
Section: Discussionmentioning
confidence: 81%
“…Nevertheless, the list of genes and causative changes identified so far cannot be considered exhaustive. Recently, defects in RC3H1 , associated with immune dysregulation and systemic hyper-inflammation syndrome, and RHOG , associated with defective lymphocyte exocytosis and HLH, have been proposed as additional causes of FHL (Kalinichenko et al 2021 ; Tavernier et al 2019 ).…”
Section: Discussionmentioning
confidence: 99%